2020
DOI: 10.1186/s12903-020-01214-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different restorative crown design and materials on stress distribution in endodontically treated molars: a finite element analysis study

Abstract: Background: The purposes of this simulation study were to evaluate the stresses in the roots of endodontically treated molars with extensive coronal tissue loss which were restored by endocrowns (all-in-one core and crown) and traditional crowns with post-cores, during masticatory simulation using finite element analysis. Methods: A mesio-distal cross-section of a lower right first molar was digitized and used to create 2-dimensional models of the teeth and supporting tissue; different crown designs, viz., end… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
(41 reference statements)
1
23
0
1
Order By: Relevance
“…It was observed that the filling material with a high elastic modulus (RC, BF, AK, FRC) allowed less stress magnitude to reach the cement layer; however, it increased the stress magnitude in the tooth substrate as well as in the restoration. In addition, the literature reports that more flexible restorative materials could be a promising option for the promotion of adequate biomechanical behavior for the endocrown restorations [ 3 , 4 , 6 , 15 , 18 , 22 ]. This study complements this finding, showing that the filling material stiffness can also modify the stress concentration in the restoration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was observed that the filling material with a high elastic modulus (RC, BF, AK, FRC) allowed less stress magnitude to reach the cement layer; however, it increased the stress magnitude in the tooth substrate as well as in the restoration. In addition, the literature reports that more flexible restorative materials could be a promising option for the promotion of adequate biomechanical behavior for the endocrown restorations [ 3 , 4 , 6 , 15 , 18 , 22 ]. This study complements this finding, showing that the filling material stiffness can also modify the stress concentration in the restoration.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the literature reporting endocrown preparations with different central retainer angulation, ranging from 6° to 12° of divergence [ 7 , 13 , 14 , 15 , 16 ], there is no mechanical reason for the selected angle parameter. Apparently, a citation chain occurred between the previous reports and there was no assessment regarding how the preparation angle can affect the restoration load dissipation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, dental implant surgery based on cone-beam computed tomography (CBCT) and three-dimensional (3D) printing surgical guide technology has been widely used in clinical practice and plays an important role in improving the accuracy of implantation and final restoration [ 1 3 ]. Any virtual implant planning system using a 3D software application in combination with implant placement by means of a computer-aided design/computer-aided manufacturing (CAD/CAM)-processed surgical guide is defined as a system for static computer-assisted implant surgery (s-CAIS) [ 4 ].…”
Section: Introductionmentioning
confidence: 99%